National government intervention in financing LGU projects with environmental objectives - Mendoza, Maria Nimfa F. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1997)
Market failures due to, among other factors, the presence of externalities, incomplete markets and ill-defined property rights provide a rationale for government intervention since private market provision will tend to lead to inefficient location and use of natural resources and the environment. Another rationale for government intervention is income redistribution which can have significant environmental impact. The paper explores the roles of the national government and local government units in financing local projects with environmental objectives. To illustrate the concepts, the cases of municipal solid waste management in Metro Manila and small watershed protection are analyzed. The rationale for national government intervention and proposed cost-sharing schemes for the different levels of government are presented for the specific projects.